Evaluating the local expression pattern of IGF-1R in tumor tissues and the circulating levels of IGF-1, IGFBP-1, and IGFBP-3 in the blood of patients with different primary bone tumors - Vaezi, Mohammad Amin; Eghtedari, Amir Reza; Safizadeh, Banafsheh; Babaheidarian, Pegah; Salimi, Vahid; Adjaminezhad-Fard, Fatemeh; Yarahmadi, Sahar; Mirzaei, Alireza; Rahbar, Mahtab; Tavakoli-Yaraki, Masoumeh (Frontiers in Oncology, 2023)
The present study tried to provide insights into the expression pattern and diagnostic significance of the IGF-1 axis main mediators in three main primary bone tumor types with different degrees of severity. The real-time qRT-PCR (to analyze IGF-1R gene expression), the immunohistochemistry (to measure IGF-1R protein) and the ELISA assay (to assess the circulating level of IGF-1, IGFBP-1 and IGFBP-3) was applied to confirm this hypothesis. The total number of 180 bone tissues (90 tumors and 90 noncancerous adjacent tissues) and 120 blood samples drained from 90 patients with bone tumor and 30 healthy controls were enrolled in the study. The association of insulin-like growth factor (IGF)-1 axis expression pattern with patient's clinical pathological characteristics and tumor aggressive features, the diagnostic and predictive values were assessed for all tumor groups. A significant elevated level of IGF-1R gene and protein was detected in bone tumors compared to the noncancerous bone tissues that was prominent in osteosarcoma and Ewing's sarcoma compared to GCT group. The positive association of IGF-1R gene and protein level with tumor grade, metastasis and recurrence was detected in osteosarcoma and Ewing's sarcoma groups. The circulating level of IGF-1, IGFPB-1 and IGFBP-3 was increased in osteosarcoma and Ewing's sarcoma and GCT groups that was correlated significantly to the tumor severity. The ability of IGF-1 axis to discriminate between bone tumors also malignant and benign tumors was considerable. In summary, our data suggested that IGF-1R, IGF-1, IGFBP-1 and IGFBP-3 levels are associated with bone tumor malignancy, metastasis and recurrence that might serve as biomarkers for osteosarcoma and Ewing's sarcoma recurrence.